Treino funcional de alcance e controle de tronco em lactentes pré-termo moderados a tardios: ensaio clínico randomizado e controlado - Sato, Natália Tiemi da Silva (Universidade Federal de São Carlos, 2021)
Introduction: Moderate to late preterm infants may present delays on the onset and development of those abilities due to possible complications of prematurity. Studies on specific abilities such as reaching and positioning experiences have shown a positive effect to optimize the reaching performance, head control and motor development in full-term and preterm infants. However, due to the relationship between manual abilities and trunk control, it is relevant to develop an intervention that emphasizes on the positioning experiences and reaching to enhance the motor development of infants at biological risk. Objective: to verify the feasibility and effect of early intervention programs on gross motor performance, trunk control and reaching performance in moderate to late preterm infants in reaching emergence. Methods: Preterm infants at the onset of reaching ability (Mean=4.36, SD=0.54 months) were randomized assigned into two groups: Functional Reaching and Trunk Control Training (experimental group-EG) and Positioning social training (control group-GC). Infants were assessed into 4 visits: 1) pre-test; 2) post-intervention 1; 3) post-intervention 2, and 4) follow-up. All assessments were performed by a blinded evaluator. The Functional Reaching and Trunk Control Training, consisting of functional activities was performed by a pediatric physical therapy and parents at home. The Positioning social training, consisting of only static positioning experiences, was performed only by parents. Parents used a daily log for both trainings (dose, frequency, duration and infant’s behavior), and responded to a parent feedback questionnaire. For the feasibility variables of early intervention programs, t-test for independent samples and the Chi-Square test were performed. For gross motor performance, the Mann-Whitney test was applied. For the segmental trunk control, the Chi-Square test was applied, and for trunk and reaching kinematics variables, the mixed linear model was used. Results: there were no differences of feasibility outcome measures for both intervention programs. Parents provide a positive feedback about both programs. At the follow-up, the EG presented higher total gross motor score than CG. Both groups improved on motor performance across time. There were no significant differences between groups in the segmental trunk control, trunk and reaching performance, but there were substantively important effects (clinically relevant). After training and at follow-up, EG infants presented higher trunk movement and smoother and faster reaching than CG. Conclusion: Both early intervention programs were considered feasible and both groups showed improvement on gross motor performance, trunk control and reaching performance across time. Substantively important effects were found, favoring Functional Reaching and Trunk Control Training, which can be an efficient early intervention strategy for clinicians.
Functional reaching and trunk control training in moderate to late preterm infants: a randomized controlled clinical trial
Keywords: Prematuro; Intervenção precoce; Desenvolvimento motor; Controle de tronco; Alcance manual; Premature; Early intervention; Motor development; Trunk control; Reaching; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL